2005
DOI: 10.1021/ol052063y
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Coupling Reactions of Bromothiophenes at the C−H Bond Adjacent to the Sulfur Atom with a New Activator System, AgNO3/KF

Abstract: [reaction: see text] Bromothiophene derivatives react with aryl iodides catalyzed by a palladium complex in the presence of a silver(I) nitrate/potassium fluoride system to induce coupling at the C-H bond, while the carbon-bromine bond is intact. The produced coupling product bearing the C-Br bond allows further palladium-catalyzed C-C bond-forming reactions in reasonable yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(56 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…The reaction of a thiophene derivative smoothly occurred with aryl iodides in the presence of silver(I) uoride and a catalytic amount of PdCl 2 (PPh 3 ) 2 to afford the corresponding arylated product in a reasonable yield. 9 Oxidative homocoupling in the absence of aryl halide was found to take place to afford the corresponding bithiophene.…”
Section: Introductionmentioning
confidence: 98%
“…The reaction of a thiophene derivative smoothly occurred with aryl iodides in the presence of silver(I) uoride and a catalytic amount of PdCl 2 (PPh 3 ) 2 to afford the corresponding arylated product in a reasonable yield. 9 Oxidative homocoupling in the absence of aryl halide was found to take place to afford the corresponding bithiophene.…”
Section: Introductionmentioning
confidence: 98%
“…In a next step we tested a protocol reported by A. Mori et al [42][43][44] who were able to couple 2-bromothiophenes with aryl iodides: the 4'-functionalized 4-iodobiphenyls were reacted with 2-functionalized thiophenes using 5 mol-% [PdCl 2 (PPh 3 ) 2 ], PPh 3 , potassium fluoride, and silver nitrate as the catalytic system to obtain the thiophenylphenylenes in moderate to acceptable yields of 58% (9) and 33% (10) (Scheme 3). Whereas the solubility of 9 is sufficient for purification via column chromatography, 10 was purified by filtering the precipitated product and repeatedly washing with various solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Chan and co-workers found that furan (79) and pyrrole (87) (Figure 17) underwent successful direct C-2 arylation with aryl bromides under a nitrogen atmosphere in the presence of 5 mol% Co(II)-A C H T U N G T R E N N U N G (tap) (tap = tetrakis-4-anisylporphirinato dianion), 10 equiv. of KOH and 100 equiv.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%